2001
DOI: 10.2170/jjphysiol.51.291
|View full text |Cite
|
Sign up to set email alerts
|

Selective Brain Cooling in Mammals and Birds.

Abstract: The term selective brain cooling (SBC) refers to the lowering of brain temperature, either locally or as a whole, below arterial blood temperature. SBC has been reported to occur in laboratory experiments on many mammalian and avian species and was often seen as a mechanism serving to protect the brain, which was more or less intuitively supposed to be more susceptible to thermal damage than other organs of the body were. So far, however, no evidence has been found showing that brain tissues are less tolerant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
73
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 45 publications
0
73
0
1
Order By: Relevance
“…For many years it was thought that selective brain cooling, in mammals or birds, functions to protect the apparently vulnerable brain from thermal damage during heat stress (for a review, see Mitchell et al, 1987). However, recent studies of free-ranging mammals in their natural habitat have yielded data that are incompatible with that concept (for reviews, see Jessen, 2001;Mitchell et al, 2002). Rather than being a process that favours protection of the brain, our current view is that selective brain cooling plays a role in whole body thermoregulation (Jessen, 2001;Mitchell et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For many years it was thought that selective brain cooling, in mammals or birds, functions to protect the apparently vulnerable brain from thermal damage during heat stress (for a review, see Mitchell et al, 1987). However, recent studies of free-ranging mammals in their natural habitat have yielded data that are incompatible with that concept (for reviews, see Jessen, 2001;Mitchell et al, 2002). Rather than being a process that favours protection of the brain, our current view is that selective brain cooling plays a role in whole body thermoregulation (Jessen, 2001;Mitchell et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely held that birds employ selective brain cooling, analogous to that in mammals. Most studies have shown that brain temperature in birds consistently is lower than core body temperature over a wide range of ambient and body temperatures (for a review, see Arad, 1990;Jessen, 2001). The anatomical structure thought to be responsible for this brain cooling is the ophthalmic rete, a network of extracranial arteries developed from the external ophthalmic branch of the internal carotid artery and closely associated with veins carrying cool blood away from the buccopharyngeal surfaces, beak and eyes (Richards, 1967;Kilgore et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cetaceans are under constant, significant thermal pressures due to their aquatic environment (Manger, 2006), whereas the artiodactyls have mechanisms in place to prevent overheating (Kuhnen, 1997;Jessen, 1998Jessen, , 2001Mitchell et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A mechanism called 'selective brain cooling' (SBC) has been described to be activated in mammals (Caputa et al, 1976;McConaghy et al, 1995;Jessen, 2001;Mitchell et al, 2002) when they face water stress. SBC is defined as brain temperature lower than arterial blood temperature (IUPS Thermal Commission, 2001), which is achieved by carotid blood cooling on its ascent to the brain (Willmer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%